Implementation of the Internet of Things (IoT) in Goods Tracking Systems at Freight Forwarding Companies - Muhammad Zulfikar; Muhammad Tohir (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
This study aims to evaluate the implementation of the Internet of Things (IoT) in a freight tracking system at a freight forwarding company. By connecting various physical devices such as sensors and GPS, IoT provides great potential to improve efficiency and visibility in the supply chain. The research method used is a qualitative method with a literature review. This research analyses the concrete benefits of implementing IoT, including improved tracking accuracy, route optimisation, and reduced delivery time. The results show that IoT can be an effective solution to overcome challenges in the modern logistics industry.